Study of the Border Adjustment of Indirect and Direct Restorations by Thermo cycling Method with Following Staying - Yulianna Enina (Journal of Global Pharma Technology, 2020)
According to modern concepts, the marginal permeability of restorations, the presence or absence of micro leaks, are the main factors determining the service life of the restoration. The restoration of teeth is subjected to several different types of stress - one of which is temperature fluctuations in the oral cavity. It is known that when eating food, brushing teeth, etc. the temperature in the oral cavity changes and affects the physical and mechanical properties of the hard tissues of the teeth, as well as of the restorative material, and in some cases leads to deformation of the zone of connection of the restorative material with the tooth surface up to its destruction. The thermal cycling procedure makes it possible to simulate the influence of this factor on the conditions of functioning of the reducing material; this is achieved by exposing the sample to a limited number of thermal cycles, which means of an artificial